Past Trauma Is Associated With a Higher Risk of Experiencing an Epileptic Seizure as Traumatic in Patients With Pharmacoresistant Focal Epilepsy - Mariotti, Sara; Valentin, Damien; Ertan, Deniz; Maillard, Louis; Tarrada, Alexis; Chrusciel, Jan; Sanchez, Stéphane; Schwan, Raymund; Vignal, Jean-Pierre; Tyvaert, Louise; El-Hage, Wissam; Hingray, Coraline (Frontiers in Neurology, 2021)
Objective: The present study aimed to evaluate the prevalence of traumatic experienced seizures (TES) and of postepileptic seizure PTSD (PS-PTSD) in patients with pharmacoresistant focal epilepsy and to explore the determining factors of TES. Methods: We conducted an observational study enrolling 107 adult refractory epilepsy patients. We used the DSM-5 criteria of traumatic events and PTSD to define TES and PS-PTSD. We assessed all traumatic life events unrelated to epilepsy, general and specific psychiatric comorbidities, and quality of life. Results: Nearly half (n = 48) of the 107 participants reported at least one TES (44.85%). Among these, one-third (n = 16) developed PS-PTSD. The TES group was more likely to experience traumatic events unrelated to epilepsy (p < 0.001), to have generalized anxiety disorder (p = 0.019), and to have specific psychiatric comorbidities [e.g., interictal dysphoric disorder (p = 0.024) or anticipatory anxiety of seizures (p = 0.005)]. They reported a severe impact of epilepsy on their life (p = 0.01). The determining factors of TES according to the multifactorial model were the experience of trauma (p = 0.008), a history of at least one psychiatric disorder (p = 0.03), and a strong tendency toward dissociation (p = 0.03). Significance: Epileptic seizures may be a traumatic experience in some patients who suffer from pharmacoresistant epilepsy and may be the source of the development of PS-PTSD. Previous trauma unrelated to epilepsy and psychiatric history are determining factors of TES. These clinical entities should be explored systematically.